2014
DOI: 10.1007/s00705-014-2230-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of JC polyomavirus large T antigen sequences among Iranian patients with central nervous system tumors

Abstract: The human neurotropic JC virus (JCV) is of significant interest due to its experimental neuro- oncogenic potential. In clinical samples from human central nervous system (CNS) tumors, detection of JCV sequences suggests a possible association with CNS neoplasms, but the results are discrepant worldwide. To assess the prevalence of JCV sequences in Iranian patients with primary and metastatic CNS malignancies, a total of 58 fresh CNS tumors were examined by quantitative real-time PCR targeting the JCV large T a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 42 publications
1
23
0
1
Order By: Relevance
“…For example, Delbue et al found that age has no significant effect on the molecular prevalence of polyomaviruses [18]. Contrary to that, Sadeghi et al reported that seroprevalence of JCPyV in Australian population increases from 60 to 68% in middle-ages and then decrease to 64% in oldest ages [45]. Although a similar trend was noticed in our study, rate of JCPyV infection in our target population was much lower than the Australian cohort.…”
Section: Discussionsupporting
confidence: 64%
“…For example, Delbue et al found that age has no significant effect on the molecular prevalence of polyomaviruses [18]. Contrary to that, Sadeghi et al reported that seroprevalence of JCPyV in Australian population increases from 60 to 68% in middle-ages and then decrease to 64% in oldest ages [45]. Although a similar trend was noticed in our study, rate of JCPyV infection in our target population was much lower than the Australian cohort.…”
Section: Discussionsupporting
confidence: 64%
“…The JCPyV LTag DNA load was determined as the viral DNA copies/RNase P gene copy (a proven single copy gene), which described the copy number/cell. Construction of plasmids containing cloned target sequences of JCPyV LTag and human RNase P gene (quantitative standards for real-time PCR) was described previously [27,28]. Quantitative real-time PCR was conducted using a Rotor-Gene ® Q (Qiagen GmbH, Hilden, Germany) real-time PCR system by the primer sets and TaqMan probe specific for the JCPyV LTag gene and the human RNase P gene according to a previously described procedure [29,30].…”
Section: Jcpyv Quantitative Real-time Pcrmentioning
confidence: 99%
“…Sólo el año 2014 fue posible encontrar en Medline reportes con cinco protocolos distintos para la detección de estos polyomavirus en muestras clínicas [24][25][26][27][28] . Esto se debe a que existe una importante diversidad de secuencias y no se ha establecido regiones conservadas absolutas.…”
Section: Discussionunclassified